User interface using bounce for realistic movement on smart TV. (2018) - Ryu, Daehyun; Park, Kyoungju
In this research, we designed the various movements on the screen based on a touch pad of a smart TV. Due to the increment of smart TV, diverse interfaces are applied on the screen and movement is the crucial part of the interfaces. However, the screen is comprised of pattern as a button; the availability of new interface is less effected for users. Therefore, it is necessary to research new screen composition to escape the existing one. Smart TV's screen layout suggests new directional properties such as moving the position where we want with simple gesture. Moreover, we found the fact in this research that less change from movement of many objects is showed compared with existing movement. Based on the result of this research, it is possible to show the motion of various effects and two-dimensional movement better than existing one-dimensional movement.